Can static type systems speed up programming? : an experimental evaluation of static and dynamic type systems - Kleinschmager, Sebastian (Anchor Academic Pub., 2013)
Hauptbeschreibung Programming languages that use the object-oriented approach have been around for quite a while now. Most of them use either a static or a dynamic type system. However, both types are very common in the industry. But, in spite of their common use in science and practice, only very few scientific studies have tried to evaluate the two type systems' usefulness in certain scenarios. There are arguments for both systems. For example, static type systems are said to aid the programmer in the prevention of type errors, and further, they provide documentation help for, the.